Development, Evaluation, and Application of Lateral-Flow Immunoassay (Immunochromatography) for Detection of Rotavirus in Bovine Fecal Samples - Al-Yousif, Yousif (American Society for Microbiology, 2002)

(untitled)
A lateral-flow immunoassay (LFT) was developed to detect bovine rotavirus in fecal samples. Using samples (n = 74) from diarrheic calves, a comparison of the LFT with a commercial latex agglutination test (LAT) and transmission electron microscopy (EM) was conducted. When EM was used as the reference method, initial studies of 29 samples indicated 70 and 80% sensitivities of the LFT and LAT, respectively, with both being 100% specific. When the LAT was the reference test, the LFT was 75% sensitive and 91% specific. Additional specimens (n = 45) were tested by the LFT and LAT alone, and results were identical for both methods.